GREEN INFRASTRUCTURE IMPLEMENTATION TO INCREASE SUSTAINABILITY IN THE CITY OF SURABAYA (CASE STUDY: FLORA PARK) - Lynda Refnitasari (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2025)
The rapid development of cities not only has an impact on the improvement of economic aspects, but also brings quite serious problems, especially the decline in environmental quality. To ensure that the condition of the urban environment is maintained, regulations are implemented, one of which regulates the availability of green open space. This regulation comes under the aim of limiting the built-up areas in urban areas so that open spaces can be used for planting and can be made available to the public for social and recreational activities. Objectives: The objective of this study was to identify the application of green infrastructure as part of the green open space in Surabaya. Methodology and results: The method used in this research is descriptive qualitative by collecting data directly through field observation or indirectly through literature study. The location taken for this research was Flora Park in Surabaya. The results of the observations show that the park implements well the green infrastructure concept such as the use of environmental paving block, perforated pipes, xeriscaping, rainwater harvesting, tree canopy, reservoir, and supportive waste management system. Conclusion, significance and impact study: It is important to pay attention to the maintenance of the park so that it remains align with its function and use.